Rethinking Le Corbusier: Urban Design and History - Sequeira, Marta (2017)
It is generally assumed that Le Corbusier’s urban planning made a break with the past, and that the public spaces designed by him had nothing to do with anything that existed before – a conviction fostered by both the innovative character of his proposals and by the proliferation in his manifestos of watchwords that mask any evocation of the past – words like civilisation machiniste, l’esprit nouveau, l’architecture de demain. However, in his writings, Le Corbusier often mentioned the powerful analogy that exists between the architecture of other times and the logic of modern production. Vers une architecture, for example, contains a mixture of photographs showing silos, cars, aeroplanes, ships (i.e. the fruits of 19th and 20th century civil architecture and mechanical engineering) alongside photographs of Greek and Roman buildings. While Le Corbusier, at the end of the 1920s, claimed “I have only one teacher: the past; only one education: the study of the past”, a series of sketches in the first volume of the Œuvre complète, done during his youth at the archaeological sites visited during his Grand Tour, shows that his interest in the past went far beyond a simple reference.